Forward Looking Behavior And Empirical Household Consumption Function - Insong Jang (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
Modern consumer theories are built upon the premise of the forward looking behavior of households. While most of the empirical studies at micro level are based on Euler equation, there have been few to estimate the household consumption function and test the implication of forward looking behavior directly. One of the main difficulties is that forward looking behavior involves such variables as human wealth and income uncertainty which are not directly observable. This paper exploits the rotating panel feature of Consumer Expenditure Survey to construct the proxies and test significance of them in the household consumption function. We fail to find evidence to support forward looking behavior over long horizon.
Keywords: D12; D91; E21; 330; Consumption Function; Uncertainty; Human Wealth